PERAN MAJELIS TAKLIM MUJAHIDAH PUTIH TERHADAP PENINGKATAN RELIGIUSITAS REMAJA DI NAGARI LUNANG - Winda Aprilusi; Yusuf Afandi (KOLONI, 2022)
The taklim assembly is one of the centers of religious mental development in the community. In this case, the taklim assembly is a place for religious education that can shape human behavior, especially for the lives of teenagers in Nagari Lunang. There are still many teenagers who lack the understanding and practice of religious values. In addition, the damaged behavior of teenagers is also the background for the formation of this white mujahidah taklim assembly. The purpose of this study was to find out how the role of the white mujahidah taklim assembly on increasing adolescent religiosity in Nagari Lunang. This study uses a qualitative descriptive approach, namely by collecting data from the field related to the subject matter of the research. The informants in this study amounted to 15 people. Data collection techniques used in this study were observation, interviews and documentation. Meanwhile, for data analysis, researchers used three activity lines, namely data reduction, data presentation, and drawing conclusions. The results of this study, it was found that the role of the white mujahidah taklim assembly on increasing adolescent religiosity in Nagari Lunang, among others, was as a forum for fostering faith and piety such as increasing worship, one of which was prayer and sunnah fasting, as a place for forming morals for teenagers, for example in efforts to establish return to deviant behaviors such as changing the lifestyle of teenagers both from the way they speak, how to behave in life, although there are still some teenagers who have not been able to change their behavior in the community. as a place of family education such as making a major contribution in solving the problems experienced by the congregation. Then as a place to study Religious Studies, there are still some teenagers who do not take part in these activities and are even busy with other matters. Keywords: Taklim Assembly, White Mujahidah, Religiosity, Lunang